Profil Farmakokinetik Amikasin Pemberian Intravena Melalui Vena Sublingualis dan Coccygea pada Ular Sanca Batik (PHARMACOKINETIC PROFILE OF AMIKACIN ADMINISTERED INTRA VENOUSLY VIA SUBLINGUAL AND COCCYGEA VEINS IN BROGHAMMERUS RETICULATUS) - Wijayanti, Agustina Dwi; Rahardjo, Slamet; Rosetyadewi, Antasiswa Windraningtyas; Septyanto, Adi Tri (Jurnal Veteriner, 2014)
The research was conducted to find out the pharmacokinetic profile of amikacin in sanca batik snake(Broghammerus reticulatus) which is expected to be beneficial in the therapy management of reptiliaes.The eight of adult snakes with averages body weight of 2-14 kg were used and they were devided into twogroups (n=4). Amikacin (5 mg/kg bw) was given by sublingualis (anterior) or coccygea (posterior) venous ingroups, respectively. Blood samples were collected by intracardiac puncture to all snakes at minutes 1,5,10, 30, 60, 120, 240, 480, 960, 1440 (24 hours) and 2880 (48 hours) post administrations. Bloods werecollected using heparinized tubes and sentrifuged at 2500 G to obtain the plasma. The Plasma sampleswere stored at -200c. Plasma were firstly extracted with trichloroacetid acid solution 10% and then injectedinto High Performace Liquid Chromatography Shimadzu 6.1. The results of amikacin levels werestatistically lower on sublingualis vein administration as compared to that of coccygea vein administrationusing Student T-Test (P<0.05). The pharmacokinetic parameters were calculated with non compartementalmethod resulted for anterior application : Vd 3.6 L, clearance 0.066 mL/minute/kg, AUC 75.384 ug/mL.minute and for posterior application : Vd 0.78 L, T1/2 213.09 hours, clearance 0.427 mL/minute/kg,AUC 117.143,7 ug/mL/minute.
Keywords: pharmacokinetic profile, amikacin, snake